Rejection and truth-value gaps - Johnson, Fred (Frederick A.), author; Duke University Press, publisher (Colorado State University. Libraries, 1999)
A theorem due to Shoesmith and Smiley that axiomatizes two-valued multiple-conclusion logics is extended to partial logics.
Keywords: categoricity and completeness of theories; many-valued logic